Структуры магнитного поля химически пекулярных звезд. II. HD 98088, HD182180, HD221218, HD318107 - Глаголевский, Ю. В.
На основе литературных данных о величинах магнитного поля построены модели магнитного поля нескольких магнитных звезд разных типов пекулярности и получены параметры магнитного поля. Среди горячих объектов обнаружены различия физических условий в области магнитных экваторов и в области близмагнитных полюсов, которые пока не поддаются интерпретации. Based on literature data about the magnetic field values, models of the magnetic field of several magnetic stars of different types of peculiarity were constructed and the magnetic field parameters were obtained. Among hot objects, differences in physical conditions have been discovered in the region of the magnetic equators and in the region near the magnetic poles, which are not yet amenable to interpretation
Keywords: Астрофизика